Obtenção de ácido giberélico por fermentação em estado sólido empregando resíduo de cervejaria e farelo de arroz bruto como substratos - Werle, Leandro Bernardi (2017)
Gibberellic acid (GA3), a phytohormone belonging to the group of gibberellins is widely used in agricultural formulations, since it allows increased productivity in different types of crops. Due to the high final cost of production of GA3, new processes for the production of the hormone have been studied, among them Solid State Fermentation (SSF). Through this fermentation it is possible to increase the concentration of the GA3 obtained, as well as to use agroindustrial substrates of low commercial value abundant in the Santa Maria region as crude rice bran (CRB) and wet brewery residue (WBR). Thus, the objective of this work was to evaluate the production of GA3 by SSF using WBR and CRB substrates and using a strain of Gibberella fujikuroi. Initially the characterization of the substrates was performed, and it was possible to verify from the results that both present great potential as sources of nutrients because they are rich in carbon and nitrogen. An central composite rotational design (CCRD) was carried out, with a 23 to 3 variables totalling 17 experiments, with 3 replicates to the central point, to investigate the influence of the initial moisture content of the substrate (50 to 70 %), The proportion of rice bran in the substrate (0 to 50% by weight) and inorganic nitrogen content (0 to 2 g / kg of substrate). After 6 days of cultivation, the best GA3 yield (0.93 g / kg substrate) occurred for the conditions (65.95% moisture, 10.12% rice bran and 1.6 g N Inorganic / kg substrate). Finally, the condition of higher yield was used to verify the kinetic profile of GA3, it was possible to verify an increase in the production of the hormone, mainly from day 4, and the maximum production (1.31 g / kg of substrate) occurred on the 10th day of fermentation, with a gradual reduction in hormone production.